The Impact of Social Media on Mental Health in Young Adults: A Cross-Sectional Study of Usage Patterns and Psychological Well-Being - al rubia , Haifa Ahmed abud ali husson (American Journal of Biomedicine and Pharmacy, 2025)
Background: Social media platforms have become an integral part of the lives of young adults, with potential implications for their mental health outcomes. Understanding the relationship between social media usage patterns and psychological well-being is crucial for developing evidence-based interventions to support this population. Objective: To examine the association between social media usage patterns and mental health outcomes in young adults aged 18-25 years, including depression, anxiety, self-esteem, and sleep quality. Methods: A cross-sectional study was conducted among 847 young adults recruited from three universities. Participants completed validated questionnaires including the Patient Health Questionnaire-9 (PHQ-9), Generalized Anxiety Disorder-7 (GAD-7), Rosenberg Self-Esteem Scale, and Pittsburgh Sleep Quality Index. Social media usage was assessed through self-reported daily usage time, platform preferences, and behavioral patterns. Results: Participants averaged 4.2 hours of daily social media use. Heavy users (>6 hours/day, n = 198) showed significantly higher depression scores (PHQ-9: 12.4 vs. 6.8, p < 0.001) and anxiety levels (GAD-7: 11.2 vs. 7.1, p < 0.001) compared to light users (<2 hours/day, n = 156). Passive consumption behaviors were associated with lower self-esteem scores (r = -0.34, p < 0.001), while active engagement showed weaker negative correlations (r = -0.15, p < 0.05). Sleep quality deteriorated with increased evening social media use (r = 0.42, p < 0.001). Conclusions: Excessive social media use, particularly passive consumption and evening usage, is associated with poorer mental health outcomes in young adults. These findings suggest the need for digital wellness interventions and the adoption of mindful social media usage practices.